Wide array of T-cell subpopulation alterations in patients with alcohol use disorders. (1st May 2016) - Zuluaga, Paola; Sanvisens, Arantza; Teniente, Aina; Fuster, Daniel; Tor, Jordi; Martínez-Cáceres, Eva; Muga, Roberto
Highlights: Alcohol appears to cause quantitative changes to lymphocyte subsets. Double negative T-lymphocytes are frequently diminished in patients with AUD. Nutritional status and cocaine consumption may confound the immune alterations. Abstract: Background: Alcohol abuse impacts innate and adaptive immunity and predisposes to infections. However, prevalence and correlations of cellular immune alterations in large case series is underreported. We aimed to analyze quantitative alterations of T-lymphocyte subpopulations in patients with alcohol use disorder (AUD). Methods: cross-sectional study in patients admitted for detoxification between January 1, 2002 and December 31, 2012. Socio-demographic and alcohol use characteristics and blood samples for biochemistry, hematology and immune phenotype was obtained at admission. Results: 238 patients (79.8% M) were eligible; age at admission was 43 years (interquartile range [IQR]: 38–51 years), the amount of alcohol consumption was 180 g/day (IQR: 120–200 g/day) and median duration of AUD was 18 years (IQR: 9–25 years). Compared to healthy individuals, 50% of patients had significantly fewer double-negative (DN) T-lymphocytes (<34 × 10 9 /L) and 23% had more double-positive (DP) T-cells (>52 × 10 9 /L). In addition, 24% of patients had high number of CD8 + cells (>735 × 10 9 /L) and 13% had low CD4 + cell counts (<600 × 10 9 /L). In multivariable analysis, age, sex, serum albumin, and current cocaine use were predictors of T-cell subpopulation alterations. Women were three-times (OR = 3.5, 95%CI:1.3–9.5) more likely to present with higher DP T-lymphocytes than men. Conclusions: Quantitative alterations of T-cell subpopulations are frequent in patients seeking treatment of AUD. Assessment of cellular immunity in this population may help to identify those at increased risk of immune alterations.